TSLP, OX40L, and IL-25 in Allergic Responses - Wang, Yui-Hsi (2009)
Allergic diseases are often triggered by environmental allergens that induce dominant type2 immune responses, characterized by the infiltrated T(H)2 lymphocytes, eosinophils, and elevated T(H)2 cytokines. In addition to T(H)2 type immune responses, epithelial stress and injury linked to tissue remodelling are often observed, suggesting that epithelial cells may play important role in regulating allergic responses. Dendritic cells (DCs), the professional antigen-presenting cells with the capabilities of sampling allergens, are considered as the key player on instructing T(H)2 immune responses. Whether inflamed epithelium can regulate innate immunity, such as macrophages and DCs, which in turns instruct adaptive immunity has long been hypothesized. Studies of TSLP (thymic stromal lymphopoietin), an epithelial cells-derived cytokine, that can strongly activate DCs, provide important evidences that the epithelial barrier can trigger allergic diseases by regulating immune responses. The finding that OX40/OX40L interactions are the molecular trigger responsible for the induction and maintenance of T(H)2 responses by TSLP-activated DCs provides a plausible molecular explanation for TSLP-mediated allergy. Recent progresses in characterizing the proinflammatory IL-17 cytokine family have added an additional layer of complexity on the regulation of allergic inflammation. TSLP-DCs can induce a robust expansion of T(H)2 memory cells and strengthen functional attributes by upregulating their surface expression of IL-17RB (IL-25R), the receptor for cytokine IL-17E (IL-25), a distinct member of IL-17 cytokine family. IL-17E (also know as IL-25) produced by epithelial cells, and other innate cells, such as eosinphils, basophils, and mast cells, are shown to regulate adaptive immunity by enhancing T(H)2 cytokine productions. These exciting findings expand our knowledge of the complex immunological cascades that result in allergic inflammation and may provide novel therapeutic approaches for the treatments of allergic diseases.